Effect of Ambient Parameters on the Temperature Distribution of Photovoltaic (PV) Modules - Divine Atsu; Alok Dhaundiyal (Resources, 2019)
This paper pivots around the influence of thermal parameters on the temperature distribution of a (PV) module. The solar irradiance, ambient temperature, and heat transfer coefficient were examined for four differently manufactured solar modules. A finite element analysis of the solar system was carried out to simulate the prevailing thermal conditions. It was determined through analysis that the heat transfer coefficient had a significant effect on the boundaries of the PV modules. The temperature gradient was relatively high at the boundary, whereas the main body had the least deviation from the mean value of experimental data. The high value of irradiance is favorable for a large PV system, while the heat transfer coefficient should be low for avoiding undulation of the thermal gradient across the plate. The temperature distribution on the surface of the PV modules largely depended on the geometry and the material used for the design purpose.